The European Union Transport Policy and their Consequences for the Infrastructure Development in Poland in 2014-2020. Part 1 - Szymanowski, Wacław (Olsztyn Economic Journal, 2014)
The paper discusses the origins and future determinants of regional development, as conditioned by the present state of transport infrastructure considered as a key endogenic factor of the development of economic regions. Increased Cohesion Policy spending, at the level of EUR 82.3 billion, in the newly opened EU multiannual financial framework for 2014-2020 aims at reducing development disparities between various EU regions and, thus, enhancing the cohesion of the EUROPEAN ECONOMIC AREA. The paper outlines the evolution of the objectives of the COMMON TRANSPORT POLICY over the last 20 years, which have a significant impact on the level of spatial cohesion and contribute to better competitiveness, reliability of transport services, their safety and environmental friendliness.